Impact of climate change on the forests, the agroforestry systems and the wildlife - Quinta-Nova, L.C. (2011)
The main impacts of climate change on wildlife are: shifts and fluctuations of habitats and habitat conditions; synergetic effects between climate change and habitat fragmentation; increase number of species threatened with extinction; and changes in the distribution of most types of vegetation. In this presentation it was addressed the synergetic effects of between climate change and habitat fragmentation.